Impact of air gap, range shifter, and delivery technique on skin dose in proton therapy. Issue 2 (23rd December 2020) - Kern, A.; Bäumer, C.; Kröninger, K.; Wulff, J.; Timmermann, B.
Abstract : Objective: Side effects of radiation therapy may include skin damage. The surface dose is of great interest and contains the buildup effect. In particular, the proton therapy community requires further experimental data to quantify doses in the surface region. This specification includes the skin dose, which is defined according to ICRU Report No. 39 at 70 μm water equivalent depth. The aim of this study is to gather more knowledge of the skin dose by varying key parameters defined by the patient treatment plan. This consists of clinical aspects such as the influence of the air gap, the application of a range shifter (RS), or the proton delivery technique. Material/methods: Skin doses were determined with a PTW 23391 extrapolation chamber with three thin Kapton® entrance windows operated as a conventional ionization chamber. The impact on the skin dose for quasi‐monoenergetic pencil beam scanning (PBS) proton beams was evaluated for clinical air gaps between 3.5 and 51.1 cm. The differences in skin dose were assessed by irradiating equivalent fields with an RS of 51 mm water equivalent thickness (RS51) and without. Furthermore, the delivery techniques PBS, uniform scanning (US), and double scattering (DS) were compared by defining a spread‐out Bragg peak (SOBP). TOPAS (V.3.1.2) was used to model an IBA nozzle with PBS and to score dose to water at the surface of a water phantom. Results: For the monoenergetic fields without the application of the RS the skin dose was constant down to an air gap of 6.2 cm. A lower air gap of 3.5 cm showed a variation in skin dose by up to 2.4% compared to the results obtained with larger air gaps. With the inserted RS51 an increase in the skin dose was found for air gaps smaller than 11.3 cm. Experimentally, a dose difference of 1.4% was recorded for an air gap of 6.2 cm by inserting an RS and none. With the Monte Carlo calculations the largest dose increase was observed at the air gap of 3.5 cm with 1.7% and 4.0% relative to the skin dose results without the RS and to the largest evaluated air gap of 51.1 cm, respectively. The SOBP comparison of the beam modalities at the measuring plane at the isocenter revealed higher skin doses without RS (including RS) by up to +1.9% (+1.5%) for DS and +1.3% (+1.1%) for US compared to PBS. For all three techniques an approx. 2% rise in skin dose was observed for the largest evaluated air gap of 37.7 cm to an air gap of 6.2 cm when using an RS51. Conclusion: The study investigated aspects of skin dose of a water equivalent phantom by varying key parameters of a proton treatment plan. Parameters like the RS, the air gap, and the delivery modality have an impact on the order of 4.0% for the skin dose at the depth of 70 μm. The increases in skin dose are the effects of the contribution of the increased electron fluence at small air gaps and the emitted hadronic particles produced by the RS.